1991
DOI: 10.1007/bf00671484
|View full text |Cite
|
Sign up to set email alerts
|

Undecidability and incompleteness in classical mechanics

Abstract: We describe Richardson's functor from the Diophantine equations and Diophantine problems into elementary real-valued functions and problems. We then derive a general undecidability and incompleteness result for elementary functions within ZFC set theory, and apply it to some problems in Hamiltonian mechanics and dynamical systems theory. Our examples deal with the algorithmic impossibility of deciding whether a given Hamiltonian can be integrated by quadratures and related questions; they lead to a version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 37 publications
0
65
0
2
Order By: Relevance
“…That result led to several undecidability and incompleteness results in dynamical systems theory; all stem from Gödel's original incompleteness theorem for arithmetic through another of the Hilbert problems, the 10th Problem. Actually such examples of incompleteness and undecidability all stem from a very general Rice-like theorem proved by da Costa and Doria (1991a). However, in order to have incompleteness in physics, we must have an axiomatic framework.…”
Section: Axiomatics For Physics: Preliminary Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…That result led to several undecidability and incompleteness results in dynamical systems theory; all stem from Gödel's original incompleteness theorem for arithmetic through another of the Hilbert problems, the 10th Problem. Actually such examples of incompleteness and undecidability all stem from a very general Rice-like theorem proved by da Costa and Doria (1991a). However, in order to have incompleteness in physics, we must have an axiomatic framework.…”
Section: Axiomatics For Physics: Preliminary Stepsmentioning
confidence: 99%
“…We have used here a variant of the construction of θ and β which first appeared in da Costa and Doria (1991a). Then, we have the following corollary.…”
Section: Ff)mentioning
confidence: 99%
“…Fifth, the 'proof'of Cole's result is almost scandalously short. Finally, how Cole (and Kraïchik) arrived at their results seem to be a non-issue; it may or may not have been hard 14 . On the other hand, 1 1 A number is said to be perfect if it is equal to the sum of all its proper divisors (eg., 6 = 1 + 2 + 3; 28 = 1 + 2 + 4 + +7 + 14).…”
Section: Problem 6 Sat -The Satis…ability Problemmentioning
confidence: 99%
“…The point to note is the square root term in (14). No underlying model of computation which is not capable of precise real number computation will be able to implement the ellipsoid algorithm consistently.…”
Section: Remark 17mentioning
confidence: 99%
“…For these systems there exists in general no constructive spectral theory [12]. It may even be shown that the solution of the spectral problem then becomes undecidable in the sense of Gödel's theory [13].…”
Section: Poincare's Divergencesmentioning
confidence: 99%